Information Integration Technology of Disaster Prevention and Mitigation System Based on Nanometer Material. Issue 1 (8th September 2021) - Xiang, Yong; Yan, Chuanjie; Su, Yangyang; Su, Zhile; Huang, Jiazhan
Abstract: The progress of science and technology makes the birth of nanometer material. In order to study the application of nanometer material in disaster prevention and mitigation, this paper proposes the research on the disaster information integration technology of disaster prevention and mitigation system based on nanometer material. This paper introduces the disaster information integration technology of the disaster prevention and mitigation system based on nanometer material. In order to highlight the advantages of the disaster prevention and mitigation system based on nanometer material, this paper carries out the function test and performance test. In the aspect of performance test, this paper compares it with the disaster prevention and mitigation system of other two materials from the aspects of response time and accuracy research. In this paper, we find that the response time of the disaster prevention and mitigation system based on nanometer material is faster than that of the other two systems, and the accuracy of the system in this paper will not be greatly reduced with the increase of task amount, which is relatively stable. Among them, when the task amount is 10, the accuracy of the system in this paper is 0.96, and when the task amount is 150, the accuracy of this system is 0.94. The results of this paper show that the disaster prevention and mitigation system based on nanometer material is relatively superior.